The model for random packaging of small-seeded crops’ seeds in the reservoir of selection seeders sowing unit - Yaropud, Vitalii; Яропуд, Віталій Миколайович; Honcharuk, Inna; Гончарук, Інна Вікторівна; Datsiuk, Dmytro; Дацюк, Дмитро Анатолійович; Aliiev, Elchyn; Алієв, Ельчин Бахтияр огли‬‬ (Estonian Academic Agricultural Society, Estonia, 2022)
The sowing unit is one of the most important working bodies of the drill. It is used to select from the total mass of a certain number of seeds and the formation of their output flow with the specified parameters. Therefore, the advantages and disadvantages of seeders, in terms of the quality of seed distribution in a row and general in the sown field, are mainly determined by the work of sowing machines. The research was carried out to develop a model of random packing of seeds of small-seeded crops in the tank of the sowing apparatus of the selection drill. The research was conducted based on numerical simulation in the software package of the CAE-system Simcenter STAR-CCM +. Because of research, the mathematical model of casual packing of seeds of small-seeded cultures in the capacity of the sowing device of a selection seeder is developed that allowed defining the equation of regression of its density from the effective diameter of seeds and coefficient of variation of this diameter. As a result of research of process of work of the batcher of the sowing device of a selection seeder regularity of change of its throughput from an angle of inclination of a gate, type of a form of executions (triangle, semicircle, rectangle) in the form of a polynomial of the third degree are received. It is established that the choice of the triangular shape of the dispenser allows for ensuring the highest accuracy of seed dosing. Висівний агрегат є одним із найважливіших робочих органів сівалки. Використовується для відбору із загальної маси певної кількості насіння та формування їх вихідного потоку із заданими параметрами. Тому переваги та недоліки сівалок щодо якості розподілу насіння в рядку та в цілому по засіяному полю в основному визначаються роботою посівних апаратів. Дослідження проводили з метою розробки моделі випадкового укладання насіння дрібнонасіннєвих культур у ємність висівного апарату добірної сівалки. Дослідження проводили на основі чисельного моделювання в програмному комплексі CAE-системи Simcenter STAR-CCM+. За результатами досліджень розроблено математичну модель випадкового закладання насіння дрібнонасіннєвих культур в ємність висівного апарату селекційної сівалки, що дозволило визначити рівняння регресії його щільності від ефективного діаметра насіння та коефіцієнта варіації. цього діаметра. У результаті дослідження процесу роботи дозатора висівного апарату селекційної сівалки встановлено закономірність зміни його пропускної здатності від кута нахилу заслінки, типу форми виконань (трикутник, півколо, прямокутник) у отримано форму многочлена третього степеня. Встановлено, що вибір трикутної форми дозатора дозволяє забезпечити найвищу точність дозування насіння.
Модель довільного пакування насіння дрібнонасіннєвих культур у резервуар висівного агрегату селекційної сівалки
Keywords: seeds; насіння; sowing unit; висівний агрегат; model; модель; random packing; довільна упаковка; parameters; параметри; efficiency; ефективність